Repeated sprint ability evaluation in soccer - Bortolotti, Henrique (2017)
The most of team sports football, basketball, handball) is characterized by intermittency, fluctuating between brief periods of maximum effort or near the maximum followed by periods and forms of recovery. Some authors have proposed several tests to measure the ability of these athletes to perform repeated sprints (repeated sprint ability - RSA), which would be directly related to the decisive moments during match. Then, this study aimed to describe the different test protocols to assess RSA in soccer players, based on original articles and reviews selected in some databases (Medline). Therefore, we suggest four protocols, two involving sprints linear (Aziz et al. 2008; Reilly, 2001) and two involving sprints with changes of direction (Bangsbo, 2008; Impellizzeri et al., 2008) to evaluate the RSA in soccer players, generating important performance parameters, which allow to develop training programs to improve that capacity. We also recommend the use of average and/or total time as a general measure of ability to perform repeated sprints and the partial duration of each sprint to identify strengths and weakness of each athlete.